Construction of heterostructure based on hierarchical Bi2MoO6 and g-C3N4 with ease for impressive performance in photoelectrocatalytic water splitting and supercapacitor. Issue 8 (7th April 2020) - Murugan, C.; Karnan, M.; Sathish, M.; Pandikumar, A.
Abstract : This work demonstrates the formation of g-C3 N4 /Bi2 MoO6 heterostructure for water splitting and supercapacitor; which shows highest PEC efficiency and symmetric device delivered a energy density and power density of 47 W h kg −1 and 4.5 kW kg −1 . Abstract : Herein, we report the synthesis of a nanohybrid material with hierarchical Bi2 MoO6 and g-C3 N4 by a solvothermal method. It shows impressive performance towards photoelectrocatalytic water splitting and supercapacitor applications due to the formation of type-II heterostructures, a higher surface area of 60.7 m 2 g −1 (Bi2 MoO6 – 44.0 m 2 g −1 ) and higher wettability. The formation of type-II heterostructures reduces the electron–hole recombination and boosts up the interfacial charge transfer in g-C3 N4 /Bi2 MoO6, and the nanohybrid material (10 wt% g-C3 N4 ) shows about 7- and 20-fold higher PEC efficiency than that of Bi2 MoO6 and g-C3 N4 under illumination (100 mW cm −2 (AM 1.5G)). Besides, due to the combination of non-faradaic and faradaic processes, g-C3 N4 /Bi2 MoO6 (5 wt% g-C3 N4 ) exhibits a high specific capacity of 1628 C g −1 at a current density of 2 A g −1 in a three-electrode configuration. The symmetric supercapacitor delivers a maximum cell voltage of 1.8 V with a high energy density and a power density of 47 W h kg −1 and 4500 W kg −1, respectively, and also shows excellent electrochemical stability with 90% capacitance retention even after 10 000 cycles at a current density of 5 A g −1 .